Efecto de la deforestación ribereña sobre la materia orgánica particulada gruesa en quebradas con influencia ganadera de la región Andina de Colombia - Giraldo, Lina Paola (2022)
Introduction: Coarse particulate organic matter originated in riparian vegetation is the main source of energy in many headwater streams. However, the transfer of such material is altered by the destruction of forests. Objective: To assess flow differences of this organic matter in streams with forests and grasslands. Methods: We compared input, storage and export of this organic matter in the riparian belts of streams with forests, and streams with grasslands, in the central Andean region of Colombia. For each stream, we measured vertical and lateral litter with baskets; stream bed litter with a quadrant, and matter export with drift nets, in a 100 m reach. Results: The streams with riparian forest received an average of 915 g m-2 of coarse particulate organic matter annually, exported a total of 334 g m-3 and stored 732 g m-2, values that were significantly higher than in grassland streams, where the corresponding values were: 125.4 g m-2; 128 g m-3 and 205.5 g m-2. Conclusions: The removal of tree cover from the riparian zone reduced the organic matter in these headwater streams of Colombia.